Legal Review Of Fictitious Transactions On Marketplace (Tokopedia Voucher Case Study) - Thohari, Amin; Cornelis, Vieta I; Marwiya, Siti (Ipso Jure, 2024)
This study discusses cases of fictitious transactions through the misuse of vouchers on e-commerce platforms. The perpetrators use various methods to create fake transactions such as creating fake accounts, using stolen identities, and manipulating vouchers. This research not only provides in-depth insight into the modus operandi of perpetrators and system weaknesses, but also helps to develop more effective law enforcement strategies and more comprehensive policies. The formulation of this research problem is: 1) What is the validity and strength of evidence in civil disputes related to fictitious transactions on the Tokopedia marketplace? 2) What is the legal review of the agreement and responsibilities of the parties in fictitious transactions on the Tokopedia marketplace? This study uses normative research to understand, interpret, and evaluate applicable legal norms. Based on the analysis and case studies that have been conducted, it is found that the strength of evidence in civil disputes related to fictitious transactions is greatly influenced by several main factors, namely the authenticity, integrity, relevance, and reliability of electronic evidence. The implementation and settlement of civil disputes related to fictitious transactions on Tokopedia involves cooperation between e-commerce platforms, consumers, and lawyers to collect legal evidence, conduct mediation, and, if necessary, take litigation routes to demand the restoration of consumer rights in accordance with the provisions of civil law